Learning innovations for identifying and developing talent for university - Henry, M.; Gibson, David; Flodin, C.; Ifenthaler, D. (InTechOpen, 2018)
As a response to global and local imperatives for organizational, operational and social change facing education today, learning innovations developed by Curtin University’s Learning Futures team offer examples of new technology-enhanced learning experiences used to identify and develop talent for university. The innovations presented are helping to re-set school-university relationships to a focus on direct, scalable and personalized digital learning services, delivered via interactive technologies that utilize game-based and team-based learning approaches. Two frameworks are proposed: one for collecting and evaluating evidence of a future ready learner; and one for situating technology innovations across five domains of higher education learning and teaching. The case study indicates that new educational technology innovations can support an expansion of the university’s mission, as well as its academic, research and service-based strategic actions, by enabling a continuum of potential entry points for learners of all ages, accessible anywhere at any time.